Approximation of Functions by Some Types of Szasz-mirakjan Operators - Al-Saidy, Sahib; Dawood, Salim (Al-Nahrain Journal of Science, 2012)
In this paper, we study the approximation of continuous functions by using some types ofSzasz-Mirakjan operators (modified Szasz-Mirakjan operator and modified mulit Szasz-Mirakjanoperator) defined on some normed space.